Effect of maintaining supervised gym- and home-based exercises on the seasonal variations of metabolic outcomes in overweight and obese Japanese adults. Issue 1 (1st October 2020) - Honda, Hiroto; Igaki, Makoto; Komatsu, Motoaki; Tanaka, Shin-ichiro
Abstract : Objectives: This study aimed to examine whether maintaining supervised gym- and home-based exercises for an extended time of period could decrease seasonal variations of metabolic outcomes in overweight and obese Japanese adults. Methods: This retrospective study recruited 54 overweight and obese outpatients who started exercising in 2006–2010 and analysed their metabolic outcomes for 5 years from March 2011 to February 2016. In this group, 26 participants performed moderate-intensity aerobic exercise (MIAE) for 30–40 min/day for at least 2 days/week, supervised by physical therapists at a hospital gym (GYM) during the observation period. Conversely, 28 participants were asked to perform MIAE by themselves at or around their homes (HOME) for the same duration. Results: The body mass index (BMI), waist circumference and homoeostasis model assessment of insulin resistance (HOMA-IR) values in winter were higher than those in other seasons in the HOME group but not in the GYM group. The annual ranges of BMI, waist circumference, fasting plasma glucose and HOMA-IR in the GYM group were smaller than those in the HOME group. Conclusion: Maintaining supervised gym-based exercise, as opposed to home-based exercise, may decrease seasonal variations of some metabolic outcomes in overweight and obese Japanese adults.